BIMBINGAN KONSELING HOLISTIK UNTUK MEMBANTU PENYESUAIN DIRI MUALAF TIONGHOA MESJID MUHAMMAD CHENGHO PALEMBANG - Neni Noviza (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2013)
This study aims to determine how the adjustment itself on converts . Subjects were converts tionghoa mosque Muhammad Chengho Palembang. This study is a qualitative study with a phenomenological approach . Data were obtained and collected through semi-structured interviews and observations by using the interview guide and checklist list . Then , the data were analyzed using analysis of data reduction , display / presentation of data and making conclusions / verification of interactive models of Miles & Huberman ( 1992 ) . The results showed that the problems experienced by the Muslim convert Muhammad Cheng Ho Mosque is a matter of family , career and employment issues , and marginalized by other communities. The Individuals who have a religious conversion